Preparation method of high-performance biomass-based hard carbon negative electrode material
By using bamboo as the precursor, a high-performance biomass-based hard carbon anode material was prepared, and combined with modified crosslinked polyimide as the binder, the problems of high cost of hard carbon anode material and low distribution of biomass precursors in the prior art were solved, and the cost reduction and performance improvement of sodium ion batteries were achieved, and its application in large-scale energy storage fields was promoted.
Patent Information
- Application Number
- CN202510143529.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-10
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2045-02-10
AI Technical Summary
The precursors of existing hard carbon anode materials are costly and complex in processes, and the distribution of biomass precursors is not wide, which limits the application of sodium ion batteries in large-scale energy storage fields.
Rich, cheap and renewable bamboo is used as the precursor, and pre-carbonization and carbonization are performed under the protection of inert gas to prepare high-performance biomass-based hard carbon anode material, and modified crosslinked polyimide is used as the binder to improve the electrochemical performance of the battery.
It reduces the cost of sodium ion batteries, improves its competitiveness in the energy storage market, significantly improves the first Coulomb efficiency and capacity retention rate of the battery, and promotes the application of sodium ion batteries in large-scale energy storage fields.
Smart Images

Figure CN119601586A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of ion batteries, and in particular relates to a method for preparing a high-performance biomass-based hard carbon negative electrode material. Background Art
[0002] The hard carbon negative electrode has become a key material for sodium-ion batteries to replace lithium-ion batteries in the field of large-scale energy storage due to its advantages such as stable structure, low working potential, high specific capacity and high tap density. At present, hard carbon precursors are mainly resins and biomass. For example, the invention patent with application number CN202110287252.7 discloses a nano-carbon composite resin hard carbon electrode material and its preparation method and application. Resin precursors have the characteristics of high purity and high carbon content, but they are expensive and complex in process, which is not conducive to large-scale commercial use and the low-cost advantages of sodium-ion batteries, and cannot improve the competitive advantage of sodium-ion batteries. In addition, the invention application with application number CN202311660219.X discloses a hard carbon electrode material with a wide interlayer spacing and its preparation method, and the precursor is coconut shell. However, coconut shells are not produced in abundance in my country, which will eventually limit the development of hard carbon negative electrodes. Therefore, biomass precursors should have the advantages of wide distribution, low cost and renewable to promote the development of biomass-based hard carbon. Summary of the invention
[0003] The purpose of the present invention is to provide a method for preparing a high-performance biomass-based hard carbon negative electrode material, using abundant, cheap and renewable bamboo as a precursor, which can reduce the cost of sodium ion batteries, improve battery performance, enhance its competitiveness in the energy storage market, and promote the application of sodium ion batteries in the field of large-scale energy storage.
[0004] The technical solution adopted by the present invention to achieve the above-mentioned purpose is: A method for preparing a high-performance biomass-based hard carbon negative electrode material comprises the following steps: S1. The bamboo precursor is heated and kept at 300 to 800° C. to obtain pre-carbonized bamboo; S2. The pre-carbonized bamboo was crushed to obtain pre-carbonized bamboo particles, the pre-carbonized bamboo particles were soaked in an alkaline solution and an acid solution, washed to neutral and dried to obtain carbon particles; S3. The carbon particles are heated and carbonized, and then cooled to 20-30°C to obtain a hard carbon material; the hard carbon material obtained is crushed and screened to obtain hard carbon particles; S4. The hard carbon particles are stirred and mixed with a binder and a conductive agent to obtain a negative electrode material, and ultrapure water is added to obtain a mixed slurry, which is the hard carbon negative electrode material.
[0005] In step S1, the heating and heat preservation treatment of the bamboo precursor are performed under the protection of an inert gas, the inert gas is nitrogen, and the flow rate of the inert gas is controlled at 10-100 sccm; In step S1, the heating rate is controlled at 1-10°C / min, and the holding time is 2-8 h; In step S1, the preparation method of the bamboo precursor is as follows: the bamboo is crushed to obtain bamboo fibers, and the bamboo fibers are washed and dried to obtain the bamboo precursor; the diameter of the crushed bamboo fibers is in the range of 0.5 to 5 mm; the bamboo fibers are washed with deionized water and dried with a hot air flow at 50 to 100°C.
[0006] In step S2, the particle size of the pre-carbonized bamboo particles obtained by crushing is 25-35 μm; In step S2, the pH of the alkaline solution is 9-14, and the pH of the acid solution is 2-5; the immersion time of the alkaline solution is 10-24 hours, and the immersion time of the acid solution is 10-24 hours; In step S2, deionized water is used for washing; the drying temperature is 50-100°C, and the drying time is 10-24 hours.
[0007] In step S3, the heating and carbonization of the carbon particles are performed under the protection of an inert gas, the inert gas is nitrogen, and the flow rate of the inert gas is controlled at 10-100 sccm; In step S3, the heating rate is controlled within the range of 1-10°C / min, the carbonization temperature is controlled within the range of 1000-1600°C, and the carbonization time is 1-5 h; In step S3, the hard carbon material is crushed mechanically or by air flow; the particle size of the obtained hard carbon particles is 5-15 μm.
[0008] In step S4, the conductive agent is one or more of Super P, graphene, acetylene black, Ketjen black, conductive carbon black, and carbon nanotubes; In step S4, the mass ratio of hard carbon particles, binder, and conductive agent is 1-10:0.5-1.5:0.5-1.5; In step S4, the solid content of the obtained mixed slurry is 40%-80%; In step S4, the stirring speed is 150-300 r / min, and the stirring time is 5-24 h.
[0009] In step S4, the binder is one or more of sodium alginate, sodium carboxymethyl cellulose, cross-linked polyimide, and modified cross-linked polyimide; the modified cross-linked polyimide is obtained by polymerization and imidization of a dianhydride compound with 1,5-diaminonaphthalene and / or 2-(4-aminophenyl)-5-aminobenzimidazole.
[0010] By adopting the above technical scheme, bamboo precursors are prepared from abundant, cheap and renewable bamboo for the preparation of bio-based hard carbon materials, which can reduce the cost of sodium-ion batteries, improve their competitiveness in the energy storage market, and promote the application of sodium-ion batteries in large-scale energy storage fields.
[0011] The binder for preparing the negative electrode material is a modified cross-linked polyimide, which is obtained by polymerization and imidization of a dianhydride compound with 1,5-diaminonaphthalene and / or 2-(4-aminophenyl)-5-aminobenzimidazole; it can improve the electrochemical performance of the resulting sodium ion battery and significantly improve the first coulomb efficiency and capacity retention rate of the battery. This may be because the modified cross-linked polyimide has good bonding strength and mechanical properties. Under the action of the cross-linking agent, the modified cross-linked polyimide helps to form intermolecular hydrogen bonds and physical entanglements, and helps to form a good conductive network in the resulting negative electrode material. In addition, the modified cross-linked polyimide obtained by reacting a dianhydride compound with 1,5-diaminonaphthalene and / or 2-(4-aminophenyl)-5-aminobenzimidazole, because the presence of groups such as benzothiazole and / or benzimidazole, helps to combine hydrogen bonds in the negative electrode material, forms a conductive network between the components of the electrode, promotes the diffusion of sodium ions during the charge and discharge process, and improves the capacity retention capacity of the electrode. In addition, the introduction of heteroatoms in the binder-modified cross-linked polyimide also contributes to the formation of hydrogen bonds in the resulting negative electrode material, providing stronger interaction forces between the components.
[0012] According to one aspect of the present invention, a hard carbon negative electrode plate is provided, comprising a current collector and a functional layer attached to the current collector, wherein the current collector is a copper foil or an aluminum foil, and the functional layer comprises the hard carbon negative electrode material obtained above.
[0013] According to one aspect of the present invention, a method for preparing a hard carbon negative electrode sheet is provided, wherein the hard carbon negative electrode material obtained above is coated on a current collector, vacuum dried and then cooled to room temperature, and cut to obtain a hard carbon negative electrode sheet for a sodium ion battery.
[0014] Preferably, the current collector is copper foil or aluminum foil, and the thickness of the current collector is 10-30 μm; the coating thickness of the hard carbon negative electrode material is 10-300 μm; the vacuum drying temperature is 50-100° C., and the drying time is 10-48 h.
[0015] According to one aspect of the present invention, there is provided a sodium ion battery, comprising a positive electrode material prepared using a sodium sheet, and the above-mentioned hard carbon negative electrode sheet.
[0016] According to one aspect of the present invention, a binder for negative electrode materials of ion batteries is provided, comprising a modified cross-linked polyimide obtained by polymerization and imidization of a dianhydride compound with 1,5-diaminonaphthalene and 2-(4-aminophenyl)-5-aminobenzimidazole.
[0017] According to one aspect of the present invention, there is provided a method for preparing a modified cross-linked polyimide, comprising the following steps: Dissolve diphenylsulfone tetracarboxylic dianhydride in dimethylacetamide (DMAc), then add 1,5-diaminonaphthalene and 2-(4-aminophenyl)-5-aminobenzimidazole, and stir and react at 20-30° C. for 10-48 hours under an argon atmosphere to obtain a modified polyamic acid; The obtained modified polyamic acid and the crosslinking agent are reacted under argon atmosphere at 20-30° C. with stirring for 4-10 hours to obtain a modified crosslinked polyamic acid; The obtained modified cross-linked polyamic acid is vacuum dried and then heated to undergo imidization reaction to obtain modified cross-linked polyimide.
[0018] Furthermore, in the process of preparing the modified polyamic acid, ethylene glycol is added to the DMAc solution of diphenyl sulfone tetracarboxylic dianhydride before adding 1,5-diaminonaphthalene and 2-(4-aminophenyl)-5-aminobenzimidazole, and the molar ratio of diphenyl sulfone tetracarboxylic dianhydride to ethylene glycol is 3-6:1.
[0019] Preferably, in the process of preparing modified polyamic acid, the mass volume ratio of diphenyl sulfone tetracarboxylic dianhydride and dimethylacetamide is 1g:0.5-3mL; the mass ratio of diphenyl sulfone tetracarboxylic dianhydride and 1,5-diaminonaphthalene is 4.5-8:1; the mass ratio of diphenyl sulfone tetracarboxylic dianhydride and 2-(4-aminophenyl)-5-aminobenzimidazole is 4.5-8:0.5-1.5.
[0020] Preferably, the cross-linking agent is trimesic acid; the mass ratio of diphenyl sulfone tetracarboxylic dianhydride to the cross-linking agent is 30-100:1.
[0021] Furthermore, when the obtained modified cross-linked polyamic acid is vacuum dried, the drying temperature is 60-90° C. and the drying time is 6-24 h.
[0022] Furthermore, during the imidization reaction of the modified cross-linked polyamic acid, the temperature is first increased to 120-160°C at a rate of 5-15°C / min, and heated at a constant temperature for 20-60min, then the temperature is continued to be increased to 200-270°C at a rate of 5-15°C / min, and heated at a constant temperature for 20-60min, and then the temperature is continued to be increased to 300-400°C at a rate of 5-15°C / min, and heated at a constant temperature for 20-60min.
[0023] Furthermore, in the preparation method of the modified cross-linked polyimide, the cross-linking agent includes trimesic acid and 2-phosphonobutane-1,2,4-tricarboxylic acid, the mass ratio of diphenyl sulfone tetraacid dianhydride to the cross-linking agent is 30-100:1; the mass ratio of trimesic acid to 2-phosphonobutane-1,2,4-tricarboxylic acid is 1:0.5-3.
[0024] Furthermore, in the preparation process of the modified cross-linked polyimide, the modified polyamic acid and trimesic acid are stirred and reacted for 2-5 hours at 20-30° C. under an argon atmosphere, and then 2-phosphonobutane-1,2,4-tricarboxylic acid is added, and the reaction is continued under an argon atmosphere at 20-30° C. with stirring for 2-5 hours to obtain the modified cross-linked polyamic acid.
[0025] In the process of preparing modified cross-linked polyimide, trimesic acid and 2-phosphonic acid butane-1,2,4-tricarboxylic acid are used as cross-linking agents. Compared with the use of trimesic acid alone as a cross-linking agent, the first coulombic efficiency and capacity retention rate of the sodium ion battery using the obtained modified cross-linked polyimide as a binder can be further improved. This may be because after adding 2-phosphonic acid butane-1,2,4-tricarboxylic acid, the cross-linking structure of the obtained modified cross-linked polyamic acid can be further changed, and the phosphonic acid group in 2-phosphonic acid butane-1,2,4-tricarboxylic acid contributes to the formation of intermolecular hydrogen bonds, and the phosphonic acid group and the related groups of 1,5-diaminonaphthalene and 2-(4-aminophenyl)-5-aminobenzimidazole in the modified polyamic acid interact with each other, which helps to increase the sodium ion intercalation site of the obtained binder and improve the ability of sodium ion embedding and de-embedding, thereby improving the electrochemical performance of the obtained sodium ion battery.
[0026] Compared with the prior art, the present invention has the following beneficial effects: 1. A bamboo precursor is prepared from abundant, cheap and renewable bamboo for preparing bio-based hard carbon materials, and a method for preparing sodium ion battery negative electrode materials using the bio-based hard carbon materials is provided, which can reduce the cost of sodium ion batteries, improve their competitiveness in the energy storage market, and promote the application of sodium ion batteries in the field of large-scale energy storage.
[0027] 2. In the process of preparing hard carbon negative electrode materials, modified cross-linked polyimide is used as a binder. The modified cross-linked polyimide is obtained by polymerization and imidization of dianhydride compounds with 1,5-diaminonaphthalene and / or 2-(4-aminophenyl)-5-aminobenzimidazole; it can greatly improve the first coulombic efficiency and capacity retention rate of the obtained sodium ion battery. The modified cross-linked polyimide has good bonding strength and mechanical properties, which is conducive to the formation of intermolecular hydrogen bonds and physical entanglements, and helps to form a good conductive network in the obtained negative electrode material; the use of 1,5-diaminonaphthalene and / or 2-(4-aminophenyl)-5-aminobenzimidazole helps the combination of hydrogen bonds in the negative electrode material, promotes the diffusion of sodium ions, and the introduction of heteroatoms also helps the formation of hydrogen bonds in the obtained negative electrode material, providing a strong interaction force between the components.
[0028] 3. In the process of preparing modified cross-linked polyimide, trimesic acid and 2-phosphonobutane-1,2,4-tricarboxylic acid are used as cross-linking agents. Compared with the use of trimesic acid alone as a cross-linking agent, the first coulombic efficiency and capacity retention rate of the sodium ion battery using the modified cross-linked polyimide as a binder can be further improved. This may be because the phosphonic acid group in 2-phosphonobutane-1,2,4-tricarboxylic acid contributes to the formation of intermolecular hydrogen bonds, and the phosphonic acid group interacts with the related groups of 1,5-diaminonaphthalene and 2-(4-aminophenyl)-5-aminobenzimidazole in the modified polyamic acid, which helps to increase the sodium ion intercalation sites of the obtained binder and improve the ability of sodium ion embedding and de-embedding, thereby improving the electrochemical performance of the obtained sodium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a SEM image of the hard carbon particles obtained in Example 1 of the present invention; Figure 2 is the XRD pattern of the hard carbon particles of Example 2 of the present invention; Figure 3 The relationship between the potential and the specific capacity of the sodium ion battery obtained in Example 1 during the first cycle of charge and discharge; Figure 4 This is the infrared spectrum of the modified polyimide obtained in Example 3. DETAILED DESCRIPTION
[0030] The technical solution of the present invention is further described in detail below in conjunction with specific implementation methods and drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0031] Example 1 Preparation of biomass-based hard carbon anode materials S1. Preparing pre-carbonized bamboo: crushing bamboo to obtain bamboo fiber, washing and drying the bamboo fiber to obtain a bamboo precursor; heating the bamboo precursor under inert gas protection and heat-treating it at 500° C. to obtain pre-carbonized bamboo; S2. Preparation of carbon particles: The pre-carbonized bamboo obtained in step S1 is crushed to obtain pre-carbonized bamboo particles, the pre-carbonized bamboo particles are soaked in an alkaline solution and an acid solution, respectively, washed to neutrality and dried to obtain carbon particles; S3. Preparation of hard carbon particles: Under inert gas protection, the carbon particles obtained in step S2 are heated and carbonized, and then cooled to 25°C to obtain a hard carbon material; the obtained hard carbon material is crushed and screened to obtain hard carbon particles; S4. Preparation of hard carbon negative electrode material: The hard carbon particles obtained in step S3 are stirred and mixed with a binder and a conductive agent to obtain a negative electrode material, and ultrapure water is added to obtain a mixed slurry, which is the hard carbon negative electrode material.
[0032] In step S1, the diameter of the bamboo fiber obtained by crushing is in the range of 0.5 to 5 mm; In step S1, the bamboo fiber is washed with deionized water and dried with a hot air flow at 80°C; In step S1, the inert gas is argon, and the flow rate of the inert gas is controlled at 80 sccm; In step S1, the heating rate is controlled at 5°C / min and the holding time is 5 h.
[0033] In step S2, the particle size of the pre-carbonized bamboo particles obtained by crushing is about 30 μm; In step S2, the pH of the alkaline solution is 12, and the pH of the acid solution is 5; the immersion time of the alkaline solution is 12 hours, and the immersion time of the acid solution is 12 hours; In step S2, deionized water is used for washing; the drying temperature is 80° C. and the drying time is 12 h.
[0034] In step S3, the inert gas is argon, and the flow rate of the inert gas is controlled at 80 sccm; In step S3, the heating rate is controlled at 5°C / min, the carbonization temperature is controlled within the range of 1400°C, and the holding time is 2h; In step S3, the hard carbon material is crushed mechanically or by air flow; the particle size of the hard carbon particles obtained by screening is 5-15 μm.
[0035] In step S4, the binder is sodium alginate, the conductive agent is conductive carbon black, and the mass ratio of the hard carbon particles, the binder, and the conductive agent is 8:1:1; In step S4, the solid content of the obtained mixed slurry is 50%; In step S4, the stirring speed is 200 r / min and the stirring time is 12 h.
[0036] In this embodiment, the SEM image of the hard carbon particles obtained at a carbonization temperature of 1400°C is shown in Figure 1 .Depend on Figure 1 It can be seen that the hard carbon particles obtained in this embodiment have irregular shapes and smooth surfaces without obvious pores, and the hard carbon particle size is about 8 μm. This irregular hard carbon structure is conducive to close accumulation on the current collector, improving the electrochemical performance of the negative electrode material of the sodium ion battery.
[0037] Preparation of hard carbon negative electrode The hard carbon negative electrode material obtained above is coated on the current collector, vacuum dried and cooled to room temperature, and a pole piece with a diameter of 15 mm is cut according to the battery size, which is the hard carbon negative electrode piece of the sodium ion battery.
[0038] Among them, the current collector is copper foil, and the thickness of the current collector is 15 μm; the coating thickness of the hard carbon negative electrode material is 100 μm; the vacuum drying temperature is 80° C., and the drying time is 12 h.
[0039] Preparation of sodium ion batteries A sodium sheet with the same size as the negative electrode sheet was used as the positive electrode material. In a glove box under an argon atmosphere, the positive electrode shell, negative electrode shell, glass fiber separator, sodium sheet (15 mm in diameter, 1 mm in thickness), and nickel foam were assembled into a CR2025 button battery according to the general operating steps. The electrolyte was a 1 M NaPF6 solution, and the solvent was a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1. The assembled battery was packaged using a button battery sealing machine.
[0040] Example 2 The difference between this embodiment and embodiment 1 is that in the process of preparing the biomass-based hard carbon negative electrode material, the carbonization temperature used in step S3 is 1100°C.
[0041] The other conditions and steps were the same.
[0042] In this embodiment, the XRD pattern of the hard carbon particles obtained at a carbonization temperature of 1100°C is shown in Figure 2 .like Figure 2 As shown in the XRD diagram 2 θ = 23° and 2 θ = 43°, a rounded mantou peak appears, indicating that the carbon obtained at this carbonization temperature is a disordered amorphous structure, which conforms to the structural characteristics of hard carbon, and the interlayer spacing is about 0.388 nm. It can be seen that the hard carbon obtained by the present invention has a larger carbon interlayer spacing, which is beneficial to improving the effective capacity of sodium ion batteries.
[0043] Example 3 The difference between this embodiment and embodiment 1 is that: in the preparation process of biomass-based hard carbon negative electrode material, in step S4, the binder is modified cross-linked polyimide, the conductive agent is conductive carbon black, and the mass ratio of hard carbon particles, binder and conductive agent is 8:1:1.
[0044] The other conditions and steps were the same.
[0045] Wherein, the preparation method of modified cross-linked polyimide is as follows: Dissolve diphenylsulfone tetracarboxylic dianhydride in DMAc, then add 1,5-diaminonaphthalene and 2-(4-aminophenyl)-5-aminobenzimidazole, and stir at 25°C and 200 r / min for 24 hours under an argon atmosphere to obtain a modified polyamic acid; The obtained modified polyamic acid and the crosslinking agent were stirred and reacted at 25° C. and 200 r / min for 6 h under an argon atmosphere to obtain a modified crosslinked polyamic acid; The obtained modified cross-linked polyamic acid is vacuum dried and then heated to undergo imidization reaction to obtain modified cross-linked polyimide.
[0046] Among them, in the process of preparing modified polyamic acid, the mass volume ratio of diphenyl sulfone tetracarboxylic dianhydride and dimethylacetamide is 1g:1mL; the mass ratio of diphenyl sulfone tetracarboxylic dianhydride and 1,5-diaminonaphthalene is 6:1; the mass ratio of diphenyl sulfone tetracarboxylic dianhydride and 2-(4-aminophenyl)-5-aminobenzimidazole is 6:1.5.
[0047] Furthermore, in the process of preparing the modified polyamic acid, ethylene glycol was added to the DMAc of diphenyl sulfone tetracarboxylic dianhydride before adding 1,5-diaminonaphthalene and 2-(4-aminophenyl)-5-aminobenzimidazole, and the molar ratio of diphenyl sulfone tetracarboxylic dianhydride to ethylene glycol was 4:1.
[0048] Furthermore, the cross-linking agent is trimesic acid, and the mass ratio of diphenyl sulfone tetraacid dianhydride to the cross-linking agent is 40:1.
[0049] When the modified cross-linked polyamic acid is vacuum dried, the drying temperature is 80° C. and the drying time is 12 h.
[0050] During the imidization reaction of the modified cross-linked polyamic acid, the temperature is first increased to 150°C at a rate of 10°C / min and heated at a constant temperature for 30 minutes, then increased to 250°C at a rate of 10°C / min and heated at a constant temperature for 30 minutes, then increased to 350°C at a rate of 10°C / min and heated at a constant temperature for 30 minutes.
[0051] IS50 Fourier transform infrared spectrometer was used to characterize the modified cross-linked polyimide. The sample was prepared by potassium bromide tablet method with a scanning wavelength range of 500 cm -1 ~4000cm -1 ; Scan line number is 32; Resolution is 4cm -1 ; The obtained infrared spectrum is shown in Figure 4 . Located at 3300cm -1 The absorption peak near is the absorption peak of OH bond. Located at 2920cm -1 and 2850cm -1The absorption peaks near are the asymmetric and symmetric stretching vibration absorption peaks of CH. Located at 1775cm -1 and 1720cm -1 The absorption peak nearby is the stretching vibration peak of the C=O bond in the imide structure. Located at 1600cm -1 and 1500cm -1 The absorption peak near is the vibration peak of the benzene ring skeleton. Located at 1370cm -1 The absorption peak near is the CN bond stretching vibration absorption peak. Located at 1240cm -1 and 1200cm -1 The absorption peaks near are the symmetric and asymmetric stretching vibration peaks of -CO-O-. -1 The absorption peak nearby is the stretching vibration peak of S=O bond. The above can prove the successful preparation of modified polyimide.
[0052] Example 4 The difference between this embodiment and embodiment 1 is that: in the preparation process of biomass-based hard carbon negative electrode material, in step S4, the binder is modified cross-linked polyimide, the conductive agent is conductive carbon black, and the mass ratio of hard carbon particles, binder and conductive agent is 8:1.2:1.
[0053] The other conditions and steps were the same.
[0054] Wherein, the preparation method of the modified cross-linked polyimide is the same as that of Example 3.
[0055] Example 5 The difference between this embodiment and embodiment 1 is that: in the preparation process of biomass-based hard carbon negative electrode material, in step S4, the binder is modified cross-linked polyimide, the conductive agent is conductive carbon black, and the mass ratio of hard carbon particles, binder and conductive agent is 8:1.5:1.
[0056] The other conditions and steps were the same.
[0057] Wherein, the preparation method of the modified cross-linked polyimide is the same as that of Example 3.
[0058] Example 6 The difference between this embodiment and embodiment 1 is that: in the preparation process of biomass-based hard carbon negative electrode material, in step S4, the binder is modified cross-linked polyimide, the conductive agent is conductive carbon black, and the mass ratio of hard carbon particles, binder and conductive agent is 8:1:1.
[0059] The other conditions and steps were the same.
[0060] Among them, the preparation method of the modified cross-linked polyimide is compared with that of Example 3, except that the cross-linking agent includes trimesic acid and 2-phosphonobutane-1,2,4-tricarboxylic acid, the obtained modified polyamic acid and trimesic acid are stirred and reacted for 3 hours at 25°C and 200r / min under an argon atmosphere, and then 2-phosphonobutane-1,2,4-tricarboxylic acid is added, and the stirring reaction is continued at 25°C and 200r / min under an argon atmosphere for 3 hours; the modified cross-linked polyamic acid is obtained; the mass ratio of diphenyl sulfone tetraacid dianhydride to the cross-linking agent is 40:1; the mass ratio of trimesic acid to 2-phosphonobutane-1,2,4-tricarboxylic acid is 1:1.
[0061] Example 7 The difference between this embodiment and embodiment 1 is that: in the preparation process of biomass-based hard carbon negative electrode material, in step S4, the binder is modified cross-linked polyimide, the conductive agent is conductive carbon black, and the mass ratio of hard carbon particles, binder and conductive agent is 8:1:1.
[0062] The other conditions and steps were the same.
[0063] Among them, the preparation method of the modified cross-linked polyimide is compared with that of Example 3, except that the cross-linking agent includes trimesic acid and 2-phosphonobutane-1,2,4-tricarboxylic acid, the obtained modified polyamic acid and trimesic acid are stirred and reacted for 3 hours at 25°C and 200r / min under an argon atmosphere, and then 2-phosphonobutane-1,2,4-tricarboxylic acid is added, and the stirring reaction is continued at 25°C and 200r / min under an argon atmosphere for 3 hours; the modified cross-linked polyamic acid is obtained; the mass ratio of diphenyl sulfone tetraacid dianhydride to the cross-linking agent is 40:1; the mass ratio of trimesic acid to 2-phosphonobutane-1,2,4-tricarboxylic acid is 1:2.
[0064] Comparative Example 1 The difference between this comparative example and Example 1 is that in the preparation process of the biomass-based hard carbon negative electrode material, in step S4, the binder is modified cross-linked polyimide, the conductive agent is conductive carbon black, and the mass ratio of the hard carbon particles, the binder, and the conductive agent is 8:1:1.
[0065] The other conditions and steps were the same.
[0066] Among them, the preparation method of the modified cross-linked polyimide is different from that of Example 3, except that 2-(4-aminophenyl)-5-aminobenzimidazole is replaced by an equal mass of 1,5-diaminonaphthalene; other conditions and steps are the same.
[0067] Comparative Example 2 The difference between this comparative example and Example 1 is that in the preparation process of the biomass-based hard carbon negative electrode material, in step S4, the binder is modified cross-linked polyimide, the conductive agent is conductive carbon black, and the mass ratio of the hard carbon particles, the binder, and the conductive agent is 8:1:1.
[0068] The other conditions and steps were the same.
[0069] Among them, the preparation method of the modified cross-linked polyimide is different from that of Example 3, except that 1,5-diaminonaphthalene is replaced by an equal mass of 2-(4-aminophenyl)-5-aminobenzimidazole; other conditions and steps are the same.
[0070] Test example The battery performance tester LAND CT3002A produced by Wuhan Landian Electronics Co., Ltd. was used to test the performance of the batteries obtained in Examples 1-7 and Comparative Examples 1-2. The test voltage range was 0.001~2.5V, and the battery performance was tested at 0.1C (1C = 372 mAg -1 ) for one cycle and calculate the first coulombic efficiency of the sodium-ion battery.
[0071] Figure 3 It is the relationship between the potential and the specific capacity during the first cycle of charge and discharge of the sodium ion battery obtained in Example 1. Table 1 shows the first coulombic efficiency of the sodium ion batteries obtained in various examples and comparative examples.
[0072] Table 1 The first coulombic efficiency of the sodium ion batteries obtained in each embodiment and comparative example
[0073] Depend on Figure 3 Combined with the data in Table 1, the discharge capacity of the sodium ion battery prepared using the hard carbon material obtained in Example 1 is higher than 300 mAh / g, and the first coulombic efficiency is higher than 85%. Therefore, the biomass-based hard carbon negative electrode material obtained in Example 1 used in the sodium ion battery has a higher capacity and first efficiency.
[0074] Referring to the data in Table 1, the first coulombic efficiency of the sodium ion battery prepared using the hard carbon material obtained in Example 2 is not much different from that of the sodium ion battery prepared using the hard carbon material obtained in Example 1. It can be seen that in the process of preparing bio-based hard carbon negative electrode materials, when the temperature of carbonizing carbon particles to obtain hard carbon particles is 1100°C or 1400°C, it has little effect on the first coulombic efficiency of the obtained sodium ion battery.
[0075] Continuing to refer to the data in Table 1, the first coulombic efficiency of the batteries obtained in Examples 3-7 and Comparative Examples 1-2 increased by 8.4%, 9.9%, 11.4%, 13.9%, 14.8%, 2.9% and 1.9% respectively compared with Example 1. It can be seen that in the process of preparing sodium ion batteries, compared with sodium alginate, using modified cross-linked polyimide as a binder can significantly improve the first coulombic efficiency of the obtained battery.
[0076] The first coulombic efficiency of the batteries obtained in Examples 3-5 is on an upward trend. It can be seen that in the process of preparing the negative electrode material of the sodium ion battery, increasing the amount of the modified cross-linked polyimide as a binder within a certain range is helpful to improve the first efficiency of the obtained sodium ion battery.
[0077] Combined with the data of Comparative Examples 1-2, the first coulombic efficiency of the battery obtained in Comparative Example 1 was reduced by 5.0% relative to Example 3, and the first coulombic efficiency of the battery obtained in Comparative Example 2 was reduced by 6.0%. It can be seen that compared with the modified cross-linked polyimide obtained by reacting 1,5-diaminonaphthalene alone or 2-(4-aminophenyl)-5-aminobenzimidazole with diphenylsulfone tetracarboxylic dianhydride alone, the modified cross-linked polyimide obtained by reacting 1,5-diaminonaphthalene and 2-(4-aminophenyl)-5-aminobenzimidazole with diphenylsulfone tetracarboxylic dianhydride has a more significant effect on the first coulombic efficiency of the sodium ion battery.
[0078] Compared with Example 3, the first coulombic efficiency of the battery obtained in Examples 6-7 was increased by 5.0% and 5.9%, respectively. It can be seen that in the process of preparing the negative electrode material of the sodium ion battery, the binder-modified cross-linked polyimide uses 1,5-diaminonaphthalene and 2-(4-aminophenyl)-5-aminobenzimidazole to react with diphenylsulfone tetracarboxylic dianhydride, and uses trimesic acid and 2-phosphonic acid butane-1,2,4-tricarboxylic acid as cross-linking agents. Compared with using only trimesic acid as a cross-linking agent, the first coulombic efficiency of the obtained sodium ion battery can be further improved; and within a certain range, the first coulombic efficiency of the obtained sodium ion battery is positively correlated with the amount of 2-phosphonic acid butane-1,2,4-tricarboxylic acid used in the preparation process of the binder-modified cross-linked polyimide.
[0079] The battery performance tester LAND CT3002A produced by Wuhan Landian Electronics Co., Ltd. was used to test the performance of the batteries obtained in Examples 1-7 and Comparative Examples 1-2. The test voltage range was 0.001~2.5V, and the battery performance was tested at 0.1C (1C = 372 mAg -1 ) current density for 180 cycles to compare the cycle stability of each sodium ion battery. Table 2 shows the capacity retention rate of the sodium ion batteries obtained in each embodiment and comparative example after 180 cycles.
[0080] Table 2 Capacity retention rate of sodium ion batteries obtained in various embodiments and comparative examples after 180 cycles
[0081] Combined with the data in Table 1, the battery prepared using the hard carbon material obtained in Example 1 still has a capacity retention rate of more than 85% after 180 cycles; therefore, the sodium ion battery using the biomass-based hard carbon negative electrode material obtained in Example 1 has good cycle stability.
[0082] Referring to the data in Table 1, the capacity retention rate of the battery prepared by using the hard carbon material obtained in Example 2 after 180 cycles is not much different from that in Example 1. It can be seen that in the process of preparing bio-based hard carbon negative electrode materials, when the temperature of carbonizing carbon particles to obtain hard carbon particles is 1100°C or 1400°C, it has little effect on the capacity retention rate of the obtained sodium ion battery.
[0083] Continuing to refer to the data in Table 1, the capacity retention rates of the batteries obtained in Examples 3-7 and Comparative Examples 1-2 were increased by 8.4%, 9.8%, 10.9%, 13.9%, 14.5%, 2.8% and 2.2% respectively, compared with Example 1. It can be seen that in the process of preparing sodium ion batteries, compared with sodium alginate, using modified cross-linked polyimide as a binder can significantly improve the capacity retention rate of the obtained battery.
[0084] The capacity retention rate of the batteries obtained in Examples 3-5 is on an upward trend. It can be seen that in the process of preparing the negative electrode material of the sodium ion battery, increasing the amount of the modified cross-linked polyimide as a binder within a certain range is helpful to improve the initial efficiency of the obtained sodium ion battery.
[0085] Combined with the data of Comparative Examples 1-2, relative to Example 3, the capacity retention rate of the battery obtained in Comparative Example 1 after 180 cycles decreased by 5.2%, and the capacity retention rate of the battery obtained in Comparative Example 2 after 180 cycles decreased by 5.8%. It can be seen that compared with the modified cross-linked polyimide obtained by reacting 1,5-diaminonaphthalene alone or 2-(4-aminophenyl)-5-aminobenzimidazole with diphenylsulfone tetracarboxylic dianhydride alone, the modified cross-linked polyimide obtained by reacting 1,5-diaminonaphthalene and 2-(4-aminophenyl)-5-aminobenzimidazole with diphenylsulfone tetracarboxylic dianhydride has a more significant effect on the capacity retention rate of the sodium ion battery.
[0086] Compared with Example 3, the capacity retention rates of the batteries obtained in Examples 6-7 were increased by 5.0% and 5.6%, respectively. It can be seen that in the process of preparing the negative electrode material of the sodium ion battery, the binder-modified cross-linked polyimide uses 1,5-diaminonaphthalene and 2-(4-aminophenyl)-5-aminobenzimidazole to react with diphenylsulfone tetracarboxylic dianhydride, and uses trimesic acid and 2-phosphonic acid butane-1,2,4-tricarboxylic acid as cross-linking agents. Compared with using only trimesic acid as a cross-linking agent, the capacity retention rate of the obtained sodium ion battery can be further improved; and within a certain range, the capacity retention rate of the obtained sodium ion battery is positively correlated with the amount of 2-phosphonic acid butane-1,2,4-tricarboxylic acid used in the preparation process of the binder-modified cross-linked polyimide.
[0087] The conventional operations in the operating steps of the present invention are well known to those skilled in the art and will not be described in detail here.
[0088] The above-described embodiments provide a detailed description of the technical solution of the present invention. It should be understood that the above-described embodiments are only specific embodiments of the present invention and are not intended to limit the present invention. Any person skilled in the art who is familiar with the present technical field can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the protection scope of the claims.
Claims
1. A method for preparing a high-performance biomass-based hard carbon negative electrode material, comprising the following steps: S1. The bamboo precursor is heated and kept at 300 to 800° C. to obtain pre-carbonized bamboo; S2. The pre-carbonized bamboo was crushed to obtain pre-carbonized bamboo particles, the pre-carbonized bamboo particles were soaked in an alkaline solution and an acid solution, washed to neutral and dried to obtain carbon particles; S3. The carbon particles are heated and carbonized, and then cooled to 20-30°C to obtain a hard carbon material; the hard carbon material obtained is crushed and screened to obtain hard carbon particles; S4. The hard carbon particles are stirred and mixed with a binder and a conductive agent to obtain a negative electrode material, and ultrapure water is added to obtain a mixed slurry, which is the hard carbon negative electrode material.
2. The method for preparing a high-performance biomass-based hard carbon negative electrode material according to claim 1, characterized in that: In step S1, the heating and heat preservation treatment of the bamboo precursor are performed under the protection of an inert gas, the inert gas is nitrogen, and the flow rate of the inert gas is controlled at 10-100 sccm; In step S1, the heating rate is controlled at 1-10°C / min, and the holding time is 2-8 h.
3. The method for preparing a high-performance biomass-based hard carbon negative electrode material according to claim 1, characterized in that: In step S2, the particle size of the pre-carbonized bamboo particles obtained by crushing is 25-35 μm; In step S2, the pH of the alkaline solution is 9-14, and the pH of the acid solution is 2-5; the immersion time of the alkaline solution is 10-24 hours, and the immersion time of the acid solution is 10-24 hours.
4. The method for preparing a high-performance biomass-based hard carbon negative electrode material according to claim 1, characterized in that: In step S3, the heating and carbonization of the carbon particles are performed under the protection of an inert gas, the inert gas is nitrogen, and the flow rate of the inert gas is controlled at 10-100 sccm; In step S3, the heating rate is controlled within the range of 1-10°C / min, the carbonization temperature is controlled within the range of 1000-1600°C, and the carbonization time is 1-5 h; In step S3, the hard carbon material is crushed mechanically or by air flow; the particle size of the obtained hard carbon particles is 5-15 μm.
5. The method for preparing a high-performance biomass-based hard carbon negative electrode material according to claim 1, characterized in that: The binder in step S4 is one or more of sodium alginate, sodium carboxymethyl cellulose, cross-linked polyimide, and modified cross-linked polyimide; the modified cross-linked polyimide is obtained by polymerization and imidization of a dianhydride compound with 1,5-diaminonaphthalene and / or 2-(4-aminophenyl)-5-aminobenzimidazole; In step S4, the conductive agent is one or more of Super P, graphene, acetylene black, Ketjen black, conductive carbon black, and carbon nanotubes; In step S4, the mass ratio of hard carbon particles, binder, and conductive agent is 1-10:0.5-1.5:0.5-1.5; In step S4, the solid content of the obtained mixed slurry is 40%-80%.
6. The method for preparing a high-performance biomass-based hard carbon negative electrode material according to claim 5, characterized in that: The preparation method of the modified cross-linked polyimide comprises the following steps: Dissolve diphenylsulfone tetracarboxylic dianhydride in dimethylacetamide, then add 1,5-diaminonaphthalene and 2-(4-aminophenyl)-5-aminobenzimidazole, and stir and react at 20-30° C. for 10-48 hours under argon atmosphere to obtain modified polyamic acid; stir and react the obtained modified polyamic acid with a crosslinking agent at 20-30° C. for 4-10 hours under argon atmosphere to obtain modified cross-linked polyamic acid; vacuum dry the obtained modified cross-linked polyamic acid, and then heat-treat it to cause imidization reaction to obtain modified cross-linked polyimide.
7. The method for preparing a high-performance biomass-based hard carbon negative electrode material according to claim 6, characterized in that: In the process of preparing modified polyamic acid, ethylene glycol is added to the dimethylacetamide solution of diphenyl sulfone tetracarboxylic dianhydride before adding 1,5-diaminonaphthalene and 2-(4-aminophenyl)-5-aminobenzimidazole, and the molar ratio of diphenyl sulfone tetracarboxylic dianhydride to ethylene glycol is 3-6:
1.
8. The method for preparing a high-performance biomass-based hard carbon negative electrode material according to claim 6, characterized in that: In the process of preparing modified polyamic acid, the mass volume ratio of diphenyl sulfone tetracarboxylic dianhydride and dimethylacetamide is 1g:0.5-3mL; the mass ratio of diphenyl sulfone tetracarboxylic dianhydride and 1,5-diaminonaphthalene is 4.5-8:1; the mass ratio of diphenyl sulfone tetracarboxylic dianhydride and 2-(4-aminophenyl)-5-aminobenzimidazole is 4.5-8:0.5-1.5; The mass ratio of diphenyl sulfone tetraacid dianhydride to the cross-linking agent is 30-100:
1.
9. A hard carbon negative electrode plate, characterized in that: It comprises a current collector and a functional layer attached to the current collector, the current collector is copper foil or aluminum foil, and the functional layer comprises the hard carbon negative electrode material according to claim 1.
10. A sodium ion battery comprising the hard carbon negative electrode sheet according to claim 9.
Citation Information
Patent Citations
Nano carbon material composite resin hard carbon electrode material as well as preparation method and application thereof
CN113161161A
Hard carbon electrode material with wide interlayer spacing and preparation method thereof
CN117623271A
Solid electrolyte, preparation method thereof and secondary battery
CN114976227A
Sodium-ion battery and preparation and application of bamboo-based composite hard carbon negative electrode active material of sodium-ion battery
CN116692828A
Hard carbon material and preparation method thereof, negative electrode material and alkali metal ion battery
CN116692830A